Leadership Influence on Work Performance in Health Care Professionals: A Narrative Review - Shamiksha; Ankitha; Mufeeda Sulthana (International Journal of Behavioral Sciences, 2025)
Leadership significantly influences the work performance of healthcare professionals by shaping job satisfaction, engagement, and organizational efficiency. This narrative review examines 21 peer-reviewed articles from PubMed and Semantic Scholar on various leadership styles—transformational, servant, democratic, digital, collective, authoritarian, laissez-faire, and caring leadership—and their impact on healthcare performance. The results indicate that transformational, servant, and democratic leadership enhance engagement, teamwork, and job satisfaction, ultimately improving performance. Digital leadership fosters employee empowerment, while caring leadership strengthens work engagement. In contrast, authoritarian and laissez-faire leadership styles are associated with higher stress and lower performance. Additionally, leadership training programs play a crucial role in developing effective healthcare leaders. The evidence highlights that positive leadership styles contribute to a committed and high-performing healthcare workforce, whereas ineffective leadership negatively impacts workplace morale. Strengthening leadership development programs can enhance healthcare outcomes.
Keywords: Job satisfaction; employee engagement; healthcare professionals; leadership styles; leadership training; work performance